STUDI KEANEKARAGAMAN OLAH TUMBUHAN BERKHASIAT OBAT DI KELURAHAN PASAR TELUKDALAM KECAMATAN TELUKDALAM - Baene, Deri Kristiani (Jurnal Sapta Agrica, 2024)
Based on the research focus, it aims to study the diversity of plants with medicinal properties in Pasar Telukdalam Village, Telukdalam District. This research aims to find out what types of medicinal plants are used by the community in Pasar Telukdalam Pasar Telukdalam Village as well as their benefits and what diseases can be cured. This type of research is qualitative with a case study approach. This research data was analyzed using data reduction, verification and drawing conclusions. The results of this research are that the types of medicinal plants used by the community in Pasar Telukdalam Village are ginger, turmeric, bitter gourd and galangal. Diseases that can be cured by medicinal plants that are used by people in Telukdalam Market Village are the ability to soothe a dry throat, overcome flatulence, overcome high stomach acid and are very good for helping to overcome coughs, shortness of breath, due to asthma, helping to relieve breathing, helps overcome nasal congestion and relieves the effects of a throbbing head due to flu. Suggestions for the community, it is hoped that this research can provide information to the community in using medicinal plants in Pasar Telukdalam Village, Telukdalam District and for Nias Raya University, it is hoped that the results of this research can enrich and add sources of information for Nias Raya University students, especially in plant processing. medicinal properties.